Economic analysis cultivation of upland rice with and without irrigation - Portugal, Jose Roberto [UNESP]; Anselmo Tarsitano, Maria Aparecida [UNESP]; Peres, Amanda Ribeiro [UNESP]; Arf, Orivaldo [UNESP]; Ferreira Rodrigues, Ricardo Antonio [UNESP] (Univ Fed Grande Dourados, 2015)
Currently, the economy factor water has been widely discussed in all nations of the world. The agricultural industry stands out as the largest consumer of fresh water through the irrigation of crops. In this context, the cultivation of rice in flooded system, which holds a large consumption of water for irrigation, is an aggravating factor for rice production in a sustainable way. Thus, this research aims to analyze economically three cultivars of upland rice with and without use of irrigation. To this end, the research was conducted in an experimental field belonging to UNESP, Campus of Ilha Solteira, in Selviria - MS, in an Typical Dystrophic Red Latosol clayed texture. For economic analysis, we used the technique of partial budgeting, based on increases in grain yields in relation to irrigation; increase in production value, according to the government's minimum price, average price of the last five years and the current price of a sack of rice husk; the cost of irrigation and gross profit margin also according to three prices on study. The use of irrigation provides productivity growth mainly to Primavera. Used in both systems (with and without irrigation), the IAC 202 had the highest yield, showing higher yield potential with and without irrigation. The Primavera cultivar has higher gross profit margin with the use of irrigation.
Keywords: cultivars; Oryza sativa L.; water management; gross profit margin